The cardiovascular work of competitive dinghy sailing - Felici, F.; Rodio, A.; Madaffari, A.; Ercolani, L.; Marchetti, M. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: Hiking is the special manoeuvre, which the dinghy sailor uses to counterbalance the capsizing effect of the wind on the boat. In the present research the work required of the heart by this exercise was studied in the laboratory using a boat simulator. METHODS: Seven Laser male sailors selected from those in the first places in the junior national rank participated in this study. Their endurance, at different levels of isometric hiking efforts, was measured. Energy expenditure due to hiking was estimated from measurements of oxygen consumption, carbon dioxide elimination and blood lactate concentration. The cardiac load was evaluated by measuring blood pressure using the conventional method and heart rate measured by electrocardiography. Cardiac output was measured using the CO2 re-breathing method. Left ventricular work was then calculated as cardiac output multiplied by mean arterial pressure. RESULTS: The most relevant result was that, while whole body cost of hiking was relatively low (about 1 IO2 min-1), the power of the heart was very significant: cardiac output almost doubled with respect to that at rest and arterial mean pressure rose from 12.5 kPa (rest) to 18.5 kPa (hiking). Thus, left ventricular power rose from 1.2 Watt to 3.2 Watt, which is a typical cardiovascular response to muscular isometric contraction. CONCLUSIONS: These results assume relevance when a person's eligibility for sailing sports is evaluated.